Trends in The Development of Evaluation in Mathematics Learning - Renita Br PeranginAngin; Robin Tarigan; Bung Heri Parhusip; Jonas Ramza Sitinjak; Tutiarny Naibaho; Ruth Mayasari Simanjuntak (Ideas Publishing, 2021)
The development of learning evaluation is determined by changes in the mathematics learning curriculum directly and changes in the national curriculum indirectly. This research is a literature study that aims to describe the trend of evaluation in mathematics learning. The evaluation of mathematics learning currently accommodates the three aspects of students' abilities, namely, attitudes, knowledge and skills as well as the assessment of its components starting from the input-process-output. Evaluation of mathematics learning in the future will also still apply authentic assessment. Perkembangan evaluasi pembelajaran ditentukan oleh perubahan kurikulum pembelajaran matematika secara langsung dan perubahan kurikulum nasional secara tidak langsung. Penelitian ini merupakan penelitian studi literature yang bertujuan untuk menggambarkan trend evaluasi dalam pembelajaran matematika. Evaluasi pembelajaran matematika saat ini mengakomodir ketiga aspek kemampuan siswa yaitu, sikap, pengetahuan dan keterampilan serta penilaian komponennya mulai dari input-proses-output. Evaluasi pembelajaran matematika ke depan juga masih akan menerapkan penilaian autentik.